Measures Identified in the Legal Acts of the European Union and Member States of the European Union for Decreasing the Risks of Money Laundering and Terrorism Financing Through Operations with Virtual Currencies - V. I. Glotov; I. Krzeckovskis (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
In studying the development of the international crime situation and the dynamics of changes in the «strategic priorities» of transnational criminal groups, it should be noted that crimes against the financial system have been and remain among the most profitable criminal acts that generate significant resources. Of particular concern to many international law enforcement agencies was the growing interest of criminals in using not only the relative and easily accessible services of banking and financial institutions, but also a fairly rapid increase in their ‘qualifications’, allowing them to be effectively used for the commission of crimes and for the legalization of funds, obtained in the course of criminal acts, complex computer technologies, including products of the rapidly developing market of crypto assets or crypto. It should be noted that the development in the recent past on the vast «cryptoprostores» of the Internet of Bitcoins (the first representative of this market) immediately caused concern and negative reaction not only of experts in the field of investment in money-laundering and financing of terrorism, but also of representatives of law enforcement bodies working in the field of combating fraud and crimes in the field of complex technologies. And such a negative reaction was due to one simple factor (which was the main advantage of bitcoins) – the possibility to purchase and carry out operations, including international ones, anonymously, as well as it is relatively easy to exchange bitcoins for ordinary funds. Unfortunately, the response of the international institutions responsible for money-laundering and the financing of terrorism, as well as those responsible for the supervision of the banking and financial sector, aimed at creating appropriate countermeasures, was significantly late, which allowed the market of crypto to begin to develop rapidly. This in turn led to a rapid growth of bitcoin-like crypto assets and a huge increase in their value, which led to some semblance of the gold rush and all the negative consequences associated with it: the bank-rotation of unlucky investors, the acquisition of fake crypto assets, large-scale theft on the exchanges of crypto, etc. That was why the need for strict regulation of the market and its inclusion in the international system against money-laundering and financing of terrorism  led responsible international organizations to take a number of measures to reduce the risks and threats of transactions with Bitcoins and its «fellow» organizations. This article presents the experience of the European Mission and individual States of the European Union in assessing risk, developing and implementing measures aimed at combating the use of crypto assets in criminal activities, as well as reducing the level of anonymity of persons engaged in transactions with this type of property.